المیول نحو المقاولاتیة لدى طالبات معاهد علوم وتقنیات النشاطات البدنیة والریاضیة - Nasri,mohamed cherif; Tiaibia,fouzi; Kecili,djamal (المجلة العلمیة لعلوم والتكنولوجیة للنشاطات البدنیة والریاضیة, 2021)
دفت الدراسة الى التعرف على مستوى المیول نحـو المقاولاتیـة لـدى طالبـات علـوم وتقنیـات النشـاطات البدنیـة والریاضـیة، والفـروق تبعـا لـبعض المتغیـرات. ولتحقیـق هدف الدراسة تم اختیار عینة عشوائیة طبقیة تكونت مـن 69طالبـة مـن جـامعتي ســوق اهــراس وعنابــة، وتــم توزیــع علــیهم اســتبیان مــن تصــمیم وتقنــین البــاحثین. وخلصت الدراسة الى أن الطالبات لدیهن میول متوسطة نحو المقاولاتیة، مع عدم وجــود فــروق دالــة إحصــائیة فــي مســتوى المیــول نحــو المقاولاتیــة تبعــا لمتغیــرات الدراســة. و أوصــى البــاحثون ضــرورة ادراج بعــض المــواد الدراســیة فــي البرنــامج الدراســي للرفــع مــن المهــارات المقاولاتیــة لــدى الطلبــة و ،و اجــراء أیــام إعلامیــة لتبیین التسهیلات و الدعم المقدم من طرف الدولة للمقاولاتیة النسویة. The study aimed at identifying the Entrepreneurial Propensity level of the female students in sciences and techniques of physical and sports activities, and to identify the differences according to some variables.To achieve the goal of the study was chosen a stratified random sample consisted of 69 students from the universities of Souk Ahras and Annaba, and the researchers distributed a questionnaire design and rationing band search.The study concluded that the students have a medium Entrepreneurial Propensity level, with no significant differences due to the study variables. The researchers recommended the need include some subjects in the course to raise entrepreneurial skills with the need for media days to demonstrate the facilities and support provided by the State for women's entrepreneurial.